Maintenance of recovered dilated cardiomyopathy patients with half-dose neurohumoral blockades (MED-CHARM): A protocol for an open-label, pilot, randomized trial - Li, Pengda; Luo, Xiaolin; Hou, Changchun; Wu, Shaofa; Wang, Luyu; Sun, Ning; Wang, Zebi; Wang, Zelan; Jin, Jun; Wang, Jiang; Qin, Zhexue (Frontiers in Cardiovascular Medicine, 2022)
Dilated cardiomyopathy (DCM) has brought great damage to the patients' health and social economy. The number of patients with recovered dilated cardiomyopathy (recDCM) has increased over the years as treatment progresses. However, there is a lack of relevant evidence to support the clinical management of patients with recDCM, thereby, the recommendations in guidelines remains sparse. Accordingly, the exploration of recDCM is important to improve patient prognosis and reduce societal burden. This is an open-label, randomized controlled, prospective study that will compare the safety and efficacy of original dose and halved dose of neurohumoral blockades for patients with recDCM. Methods An open-label, randomized controlled, prospective study will be conducted among eligible patients with recDCM. During the pilot study phase, we will recruit 50 patients. The primary endpoint is hospitalization for heart failure or heart failure relapse within 12 months. Secondary endpoint is major adverse cardiovascular events, including cardiovascular mortality, myocardial infarction, stroke, sustained atrial tachycardia, or ventricular tachycardia. The results will be analyzed using intention-to-treatment analysis. Discussion The study will provide important evidence of whether it is safe and effective to halve the dosage of neurohumoral blockades in recDCM patients. Trial registration number ChiCTR2100054051 (www.chictr.org.cn)